Pseudocapacitive Materials-Based Metal-Air Batteries - Verma S.; Pandey V.K.; Gupta R.K.; Verma S.; Verma B. (My University, 2025)
Researchers’ attraction has been sparked by the fabrication of green and renewable energy-storage innovations in view of the increasing hurdle around the needs of energy and environmental concerns. MABs (Metal-air batteries), mainly rechargeable MABs, are seen as a viable energy storage/conversion solution because of their high energy density and specific power, lower price, as well as its safety. Moreover, the fabrication of MABs is significantly hindered by their lower rate ability, corrosion, and dendrite formation between the electrochemical actions, less active material synthesis strategies expansion, slower oxygen reaction kinetics at cathode surface, electrolyte and electrode refinement, and a proper separator selection. This chapter goes into great detail to help readers understand many types of MABs, the fundamentals of electrode reactions and battery configurations, the function of electrode active materials, separators, and electrolytes, as well as future scenarios. © 2024, The Author(s), under exclusive license to Springer Nature Switzerland AG.